ИСПОЛЬЗОВАНИЕ ОПТИЧЕСКИХ МЕТОДОВ ИССЛЕДОВАНИЯ КРОВИ В ДИАГНОСТИКЕ СТАДИИ ЗАБОЛЕВАНИЯ ПРИ ДИФФУЗНОЙ ПАТОЛОГИИ ПЕЧЕНИ - М. И. Воевода; М. В. Кручинина; С. Е. Пельтек; С. А. Курилович; В. Н. Кручинин; Е. В. Спесивцев; С. В. Рыхлицкий; В. А. Володин; В. М. Генералов; В. В. Герасимов; Б. А. Князев (SINAPS LLC, 2012)
An assessment of the possibility of optical methods for studying red blood cells and serum of patients with diffuse liver disease with varying degrees of fibrosis for use in early diagnosis has been made. It is shown that the use of combined optical methods can significantly improve the performance of sensitivity, specificity, accuracy index and achieve real results in the diagnosis of both pronounced fibrosis and slight ulterior liver fibrosis. Identified opportunities of optical methods may be promising in screening non-invasive staging in diffuse liver disease of various origins.